Neo-Scholastic Conception of Philosophical Method in Lithuania - Rinkevičienė, Rūta (Problemos, 1991)
The Neo-Scholastic conceptions of philosophical method, its premises, its eclectism and contradictions are discussed in the paper. The methodological attitude of the orthodox Catholic philosophy corresponded to the intellectual position of Thomism. The unortodox Catholic philosophy was transformed by the “metalogical”, “relative” philosophy and phenomenological ideas. Therefore it moved away from the Thomistic conception of philosophical method, and was close to spiritualistic one. However, it seems that methodological attitudes of the orthodox Catholic philosophy were more consistent and rational, while the unorthodox searches of the philosophical method arose not only discussions about the peculiarity of philosophy, but new problems and ideas as well.